Інтермедіальне перекодування творів Гео Шкурупія у відеоперформансах Семінару творчої молоді 2020 p. - Гладун, Д. (Слово і Час, 2021)
У статті проаналізовано особливості поетичного перформансу в рамках Семінару творчої молоді (далі — СТМ або семінар), що у 2020 р. вперше відбувся онлайн. Охарактеризовано відмінності між перформансами, виконаними наживо, відеоперформансами та документаціями перформансів. Досліджено п’ять відеоперформансів за мотивами віршів Гео Шкурупія: «Розмова із собою майбутнім» Ярослава Борути, «Хочу бути меблею» Владислави Дем’янчук (Даді), «Ой маленький хлопчику» Наталі Мацибок-Стародуб, «Чеський скотч» Ірини Павленко (Іра Пам’ятай), «Майбутнє вишневих садків» Вікторії Фещук. Окреслено три типи інтермедіального перекодування претекстів у твори мистецтва перформансу: апелювання до претексту, але відмова від його безпосереднього використання протягом дії; повне або часткове цитування претексту; створення нового поетичного висловлювання за допомогою колажування фрагментів претекстів. The paper focuses on poetry-based video performances conducted by the participants of the “Creative Youths Seminar” (CYS), which was founded in 1995. Adaptability is one of the most essential features of all seminar clusters. It leads to constant transformations in a general program and within poetry performance laboratory (existing as a part of CYS since 2015) in particular, due to socio-cultural and political context. In 2020, because of the quarantine restrictions, CYS for the first time changed its regular face-to-face form to a remote one and took place online. Live performance cluster transformed into a three-day marathon of video performances. During that time 24 participants made over 70 video performances that lasted for more than 100 minutes in total (there was a record number in every category of a CYS performance cluster). Nearly half of the performances were poetry-based. Almost a third part was based on the poems by Ukrainian Futurist writers Oleksa Vlyzko, Mykhail Semenko, Oleksa Slisarenko, Andrii Chuzhyi, Geo Shkurupii, and Yulian Shpol. The article analyzes five poetry-based video performances that refer to the poems by Geo Shkurupii as pretexts: “A Talk with a Future Self ” by Yaroslav Boruta, “I Want to Be a Furniture” by Vladyslava Demianchuk (Dadi), “Oh Little Boy” by Natalia Matsybok-Starodub, “Czech Scotch Tape” by Iryna Pavlenko (Ira Pamiatai), and “The Future of Cherry Orchards” by Viktoriia Feshchuk. The pretexts, poetry performance texts (if any), and their intermedial connections with video performances have been examined. The researcher concludes that poetry-based performances let the artists not only experience the text traditionally but also ‘live through the text’, or, in other words, create a personal physical experience of the pretext and offer the audience another perspective on the pretext with the help of non-literary media.